Risiko Terjadinya Kebangkrutan pada Perusahaan Manufaktur Sub-sektor Tekstil yang Tercatat di Bursa Efek Indonesia dipengaruhi oleh Profitabilitas dan Likuiditas - Rista Intan Permata Sari; Rr. Adiati Trihastuti (CV. ITTC INDONESIA, 2025)
The textile manufacturing subsector is a strategic sector in the Indonesian economy. However, in recent years it has faced significant pressure due to global competition, rising production costs, and fluctuations in market demand. These conditions have impacted company financial performance and increased the risk of bankruptcy. Profitability and liquidity are important indicators in assessing a company's financial health, as they reflect the ability to generate profits and meet short-term obligations. However, previous research has shown conflicting findings regarding the influence of these two variables on bankruptcy risk. This study aims to analyze the effect of profitability and liquidity on bankruptcy risk in textile manufacturing companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach with a causal approach. The data used are secondary data in the form of company financial reports obtained from the Indonesia Stock Exchange for the 2021–2023 period. The study population includes all textile manufacturing companies listed on the IDX, with a sample of 13 companies selected using a purposive sampling technique, resulting in 39 observations. Data collection was conducted through documentary studies, while data analysis used the Partial Least Squares (PLS) method with the help of the SmartPLS application. The results of this study indicate that profitability does not significantly influence bankruptcy risk. Conversely, liquidity does. Simultaneously, profitability and liquidity do not significantly influence bankruptcy risk in manufacturing companies in the textile subsector. The conclusion of this study indicates that liquidity is a more dominant factor influencing bankruptcy risk than profitability. The implications of this research emphasize the importance of effective liquidity management by textile companies to maintain business continuity and reduce bankruptcy risk, and serve as a consideration for investors and other stakeholders in economic decision-making.